FAKTOR YANG BERHUBUNGAN DENGAN KEPEMILIKAN JAMBAN SEHAT DI DESA MALIKIAN, KALIMANTAN BARAT - Otik Widyastutik (Jurnal Ilmu Kesehatan Masyarakat, 2017)
The World Bank states that the 2010 data 22% of Indonesian people has not had a sanitation facility (latrine). The existence of latrines in Indonesia, according to World Bank data in 2010 about 22% of Indonesia's population does not have latrines. The coverage ofnational guard to urban areas with 79% and 49% for rural areas. Most of the sludge removal is using the river or dug wells which do not have the requirements of health latrine and contiminate the ground water. Based on the data obtained from the Health CenterCommunity Mempawah Hilir in 2014 of 855 homes were inspected as many as 530 households, households have basic sanitation facilities such as latrines in the Health Center Community Mempawah downstream for 420 households or 79%. This study aims todetermine the relationship between the factors of income, knowledge, and attitude, with the ownership of latrines in Malikian, Mempawah Hilir. The research method uses observational design with cross sectional approach. The sample in this study are mothers who have children under five do not have latrines that sebayak 64 respondents. The sampling technique using random sampling. Statistical analysis using chi square test. Decision of research hypothesis testing based on the significance level of 5% (p = 0.05) and confidence interval (CI) 95%. The result show that there are relationship between income and the latrine ownership (p = 0.037), knowledge(p = 0.037) and attitude (p = 0.037). The result shows no relationship between education (p = 0196), and the role of health care workers (p =1.000) with the ownership of latrines in the Malikian, Mempawah Hilir. Keywords: Latrine, income, knowledge, attitude. Keberadaan jamban di Indonesia menurut data Bank Dunia tahun 2010 sekitar 22%. Secara nasional, untuk daerah perkotaan yaitu 79 % dan untuk daerah pedesaan 49%. Sebagian besar pembuangan tinja masih dilakukan ke sungai atau mempergunakansumur galian yang tidak memenuhi persyaratan sehingga mencemari air tanah. Berdasarkan data yang di peroleh dari Puskesmas Mempawah Hilir pada tahun 2014 dari 855 rumah yang dilakukan pemeriksaan sebanyak 530 rumah tangga, rumah tangga yangmemiliki sarana sanitasi dasar berupa jamban di wilayah kerja Puskesmas Mempawah Hilir sebesar 420 rumah tangga atau 79%. Penelitian ini bertujuan untuk mengetahui hubungan antara faktor penghasilan, pengetahuan, dan sikap, dengan kepemilikan jamban di Desa Malikian, Mempawah Hilir, Kalimantan Barat. Metode penelitian menggunakan rancangan observasional dengan pendekatan cross sectional. Sampel dalam penelitian ini adalah rumah tangga yang memiliki balita yaitu sebanyak 64 responden, di ambil dengan menggunakan random sampling. Analisis statistik menggunakan uji chi square. Hasil penelitian menunjukkan bahwa adanya hubungan penghasilan terhadap kepemilikan jamban (p = 0.037), pengetahuan (p = 0.037) dan sikap (p = 0.037). Hasil penelitian menunjukkan tidak ada hubungan antara pendidikan (p = 0.196), dan peran petugas kesehatan (p = 1.000) dengan kepemilikan jamban di Desa Malikian, Mempawah Hilir. Kata kunci : Jamban, penghasilan, pengetahuan, sikap.